Association of serum leptin and ghrelin levels with smoking status on body weight: a systematic review and meta-analysis - Shaheen, Nour; Shaheen, Ahmed; Diab, Rehab Adel; Saad, Abdelrahman M.; Abdelwahab, Omar Ahmed; Soliman, Sama; Hefnawy, Mahmoud Tarek; Ramadan, Alaa; Meshref, Mostafa; Nashwan, Abdulqadir J. (Frontiers in Psychiatry, 2023)
Background and aims Smoking cigarettes is a major global health problem that affects appetite and weight. The aim of this systematic review was to determine how smoking affected plasma leptin and ghrelin levels. Methods A comprehensive search of PubMed, Scopus, Web of Science, and Ovid was conducted using a well-established methodology to gather all related publications. Results A total of 40 studies were included in the analysis of 11,336 patients. The overall effect showed a with a mean difference (MD) of −1.92[95%CI; −2.63: −1.20] and p = 0.00001. Subgroup analysis by study design revealed significant differences as well, but with high heterogeneity within the subgroups (I2 of 82.3%). Subgroup by sex showed that there was a significant difference in mean difference between the smoking and non-smoking groups for males (MD = −5.75[95% CI; −8.73: −2.77], p = 0.0002) but not for females (MD = −3.04[95% CI; −6.6:0.54], p = 0.10). Healthy, pregnant, diabetic and CVD subgroups found significant differences in the healthy (MD = −1.74[95% CI; −03.13: −0.35], p = 0.01) and diabetic (MD = −7.69[95% CI, −1.64: −0.73], p = 0.03). subgroups, but not in the pregnant or cardiovascular disease subgroups. On the other hand, the meta-analysis found no statistically significant difference in Ghrelin serum concentration between smokers and non-smokers (MD = 0.52[95% CI, −0.60:1.63], p = 0.36) and observed heterogeneity in the studies (I2 = 68%). Conclusion This study demonstrates a correlation between smoking and serum leptin/ghrelin levels, which explains smoking’s effect on body weight. Systematic review registration https://www.crd.york.ac.uk/ prospero/display_record.php, identifier (Record ID=326680).